Zaangażowanie w aktywności szkolne a funkcjonowanie w roli ucznia – wyniki badań przeprowadzonych na grupie młodzieży gimnazjalnej - Tomaszek, Katarzyna (Studia Edukacyjne, 2020)
Student school engagement is a multi-dimensional meta-construct describing identification and sense of belonging with school environment, an acceptance of the goals of schooling and students’ mental investment of physical and psychical energy into academic work and school life. The study aims to investigate the main predictors of student school engagement in the area of pupils’ school functioning. The participants were 291 secondary school children aged between 12 and 15 years. A stepwise multiple regression analysis indicated that the most important predictors of student school engagement are the time spent learning, subjective declaration about school performance, school type (private Catholic school), and quality of family and peer relations. Those variables explain 20% of the variance in the Global Student School Engagement level.